RELATIONSHIP OF OBESITY PARAMETERS AND ADIPOKINES WITH THE RISK OF 2ND TYPE DIABETES DEVELOPMENT IN A YEAR AFTER MYOCARDIAL INFARCTION - O. V. Gruzdeva; O. E. Akbasheva; D. A. Borodkina; V. N. Karetnikova; Yu. A. Dyleva; A. N. Kokov; T. S. Fedorova; O. L. Barbarash (Российский кардиологический журнал)
Aim. To study markers of insulin resistance and adipokine status in patients with visceral obesity in dynamics of hospital period of myocardial infarction and to evaluate carbohydrate metabolism changes in a year after the disease. Material and methods. Totally 94 patients studied with myocardial infarction (Ml). Type of obesity was defined with the body mass index (BMI), waist circumference (WC), area of visceral adipose tissue (VAT). At 1st and 12th day of hospitalization the glucose level, insulin, adiponectin, leptin were measured and the insulin resistance index (IR). During one-year follow-up we registered all novel cases of 2nd type diabetes (DM) onset.Results. According to computed tomography (CT) data 69% of patients with Ml have visceral obesity (VO). In contrast with such obesity parameters as BMI and WT, area of VAT is the most relevant index of the risk of DM development. It is shown that if the area of VAT in a patient is more than 130 cm then the risk of DM is 3,6 times higher. Also IR and hyperleptinemia in patients with VO lead to increased risk of DMonset in long-term post infarction period, resp., 3,5 and 3,7 times, comparing to the patients without VO.Conclusion. Visceral obesity is related to IR, increased level of leptin 5,7 times and higher risk of DM onset during a year after Ml.